Perumusan Aktivitas Capacity Building bagi Perangkat Desa, Pengurus Badan Usaha Milik Desa dan Lembaga Kemasyarakatan Desa menuju Desa Mandiri Berkelanjutan - Aman Suyadi; Erna Handayani; Naelati Tubastuvi (Prisani Cendekia, 2022)
The purpose of this community service is to help Sambirata village formulate capacity building activities needed to improve village development performance. This activity was carried out in the form of holding a Focus Group Discussion (FGD) with all elements of the government and parties related to the development of the Sambirata village. The results of the FGD obtained a SWOT analysis of the government of Sambirata Village, Bumdes Sambirata, Youth Organizations in Sambirata Village, Tourism Awareness Group (Pokdarwis) in Sambirata Village and Joint Farmer Groups (Gapoktani) in Sambirata Village. The end result is a proposed activity for the Sambirata Village capacity building program that can be used as a guide for the preparation of the Sambirata village program